Rationale and design for comparison of non-compliant balloon with drug-coating balloon angioplasty for side branch after provisional stenting for patients with true coronary bifurcation lesions: a prospective, multicentre and randomised DCB-BIF trial - Yan Wang; Qiang Wu; Xiang Chen; Fei Ye; Jun-Jie Zhang; Xiao-Fei Gao; Jing Kan; Zhen Ge; Damras Tresukosol; Muhammad Munawar; Teguh Santoso; Imad Sheiban; et al. (BMJ Open)
Introduction Provisional stenting using drug-eluting stent is effective for simple coronary bifurcation lesions. Kissing balloon inflation using conventional non-compliant balloon is the primary treatment of side branch (SB) after main vessel (MV) stenting. Drug-coating balloon (DCB) is reported to be associated with less frequent clinical events in in-stent restenosis and small vessel disease. The importance of DCB in bifurcation treatment is understudied. Accordingly, this trial is designed to investigate the superiority of DCB to non-compliant balloon angioplasty for SB after provisional stenting in patients with true coronary bifurcation lesions.Methods and analysis The DCB-BIF trial is a prospective, multicentre, randomised, superiority trial including 784 patients with true coronary bifurcation lesions. Patients will be randomised in a 1:1 fashion to receive either DCB or non-compliant balloon angioplasty if SB diameter stenosis >70% after MV stenting. The primary endpoint is the composite of major adverse cardiac event at the 1-year follow-up, including cardiac death, myocardial infarction (MI) or clinically driven target lesion revascularisation. The major secondary endpoints include all-cause death, periprocedural MI, spontaneous MI, clinically driven target vessel revascularisation, in-stent restenosis, stroke and individual component of the primary endpoint. The safety endpoint is the risk of stent thrombosis.Ethics and dissemination The study protocol and informed consent have been reviewed and approved by the Institutional Review Board of all participating centres. The written informed consent for participation in the trial will be obtained from all participants. The results of this study will be published in a peer-reviewed journal and disseminated at conferences.Trial registration number NCT04242134.